On the discovery of new low temperature monoclinic phases with Cm and Cc space groups in Pb(Zr0.52Ti0.48)O3: An overview - Pandey D.; Ragini (My University, 2025)
The decades old phase diagram of the technologically important Pb(ZrxTi1-x)O3 (PZT) ceramics in the vicinity of the morphotropic phase boundary has been under review during the last few years. This article summarises the results of the discoveries of two new monoclinic phases (FMHT) and (FMLT) with Cm and Cc space group by the Brookhaven group and our group, respectively, in the PZT ceramics.